2017
DOI: 10.12934/jkpmhn.2017.26.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Self-transcendence Enhancement Program among Patients with Drug Addiction: A Mixed Method Research

Abstract: Purpose:The purpose of this mixed method study was to examine effects of the self-transcendence enhancement program among patients with drug addiction, and to explore their experiences through the program. Methods: For the quantitative study, a non-equivalent control group quasi-experimental design was used. The sample was 49 hospitalized patients with drug addiction. The self-transcendence enhancement program was provided twice a week for 6 weeks. Quantitative data were analyzed using x 2 test, t-test and ANC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…As aforementioned, the mean self‐transcendence score of the participants was 48.23 ± 7.17. In a study by Kim and Kim (2017) that investigated 49 individuals diagnosed with SUD, the mean self‐transcendence level was found to be 42.04 ± 4.50. There is an insufficient number of studies investigating self‐transcendence in such individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As aforementioned, the mean self‐transcendence score of the participants was 48.23 ± 7.17. In a study by Kim and Kim (2017) that investigated 49 individuals diagnosed with SUD, the mean self‐transcendence level was found to be 42.04 ± 4.50. There is an insufficient number of studies investigating self‐transcendence in such individuals.…”
Section: Discussionmentioning
confidence: 99%
“…If an individual experiences an existential and/or spiritual void wherein the meaning and purpose of life are lost, they may use a substance to achieve momentary satisfaction, and this may lead to SUD. Thus, practices that promote self‐transcendence can help individuals diagnosed with the disorder overcome this spiritual emptiness and move toward recovery at a treatment center (Kim & Kim, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Another research found that higher self-transcendence had a beneficial effect on addictive disorders, such as nicotine dependence (Garland and Fredrickson 2019). Improving self-transcendence was also found to be helpful for patients with substance dependence (Kim and Kim 2017).…”
Section: Self-transcendence and Cigarette Dependencementioning
confidence: 98%
“…The effect size of the self-transcendence variable (d = .70) and the effect size of the depression variable (d = .45) suggested by Kim and Kim's [22] self-transcendence program were considered, and the lower of the two values was selected for this study. Thus, the effect size was set to d = .45, and with a significance level of α = .05 and power of .80, the minimum sample size required for a one-sided paired t-test was found to be 32 participants.…”
Section: Study Sizementioning
confidence: 99%
“…That study's framework served as a starting point for the introductions, development, conclusions, and family activities included in our program. In addition, single sessions in our program were designed to include 10 minutes for introductions, 40 minutes for development, and 10 minutes for conclusions, based on the time breakdown of a self-transcendence enhancement program for drug addicts [22]. Based on another study that conducted a social support activity program for the elderly [10], the class size for the program was small (limited to 6-7 people) to encourage active communication, support, and reassurance.…”
Section: Analysis Of the Literature And Content Of In-depth Interviewsmentioning
confidence: 99%